2018
DOI: 10.1111/plb.12712
|View full text |Cite
|
Sign up to set email alerts
|

Studies on lead and cadmium toxicity in Dianthus carthusianorum calamine ecotype cultivated in vitro

Abstract: Information on metallophytes during reclamation of land contaminated with heavy metals is sparse. We investigated the response of D. carthusianorum calamine ecotype to Pb and Cd stress. We focused on in vitro selection of tolerant plant material for direct use in chemically degraded areas. Shoot cultures were treated with various concentrations of Pb or Cd ions. Plantlet status was estimated as micropropagation efficiency, growth tolerance index (GTI) and through physiological analysis. Moreover, determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Such positive effects on CAL culture caused just by these HMs that are characteristic for calamine substrate, and simultaneously in the dose corresponding to their amounts available for plants on waste heap from tested ecotype originated, may implicate the increase requirement of CAL specimens for Zn, Pb, and Cd, i.e., those trace elements to which this ecotype has become adapted. This hypothesis was announced for the first time by Antonovics et al [41], and confirmed in later study on other metal-tolerant taxon from the Caryophyllaceae family-Dianthus carthusianorum [6]. To some extent it also explains the recently postulated phenomenon of a dose-dependent response to HMs, called hormesis.…”
Section: Morphogenetic Response Of Hm-treated Cultures Is Diversifiedmentioning
confidence: 67%
See 1 more Smart Citation
“…Such positive effects on CAL culture caused just by these HMs that are characteristic for calamine substrate, and simultaneously in the dose corresponding to their amounts available for plants on waste heap from tested ecotype originated, may implicate the increase requirement of CAL specimens for Zn, Pb, and Cd, i.e., those trace elements to which this ecotype has become adapted. This hypothesis was announced for the first time by Antonovics et al [41], and confirmed in later study on other metal-tolerant taxon from the Caryophyllaceae family-Dianthus carthusianorum [6]. To some extent it also explains the recently postulated phenomenon of a dose-dependent response to HMs, called hormesis.…”
Section: Morphogenetic Response Of Hm-treated Cultures Is Diversifiedmentioning
confidence: 67%
“…Some HMs, such as zinc (Zn), nickel (Ni), or copper (Cu), are fundamental to different physiological processes and required in trace amounts for higher plants [2]. Others, like lead (Pb) and cadmium (Cd), do not have recognized beneficial roles, although more and more research has recently indicated their positive effects on morpho-physiological traits under low-dose treatment [3][4][5][6]. Despite their biological necessity, HMs…”
Section: Introductionmentioning
confidence: 99%
“…For example, the hormesis effect of aluminium (Al) on the growth, development and biomass production of plants such as rice, tea, coffee, Melastoma malabathricum , soybean and maize was also recorded [ 44 , 51 , 52 , 53 , 54 , 55 , 56 ]. Moreover, numerous studies have reported the hormesis effect caused by Cd for plant species such as Gypsophila fastigiata , Sedum alfredii , Viola baoshanensis , Lonicera japonica , Dianthus carhusianorum , Solanum melongena , Arabis paniculata , Brassica juncea , Salsola kali, Spirodela polyrrhiza, Arabis paniculata [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. This effect was also caused by As in the case of Spirodela polyrrhiza L. [ 65 ].…”
Section: Hormesis As a Biological Phenomenon In The Context Of Orgmentioning
confidence: 99%
“…Besides, numerous experiments with chromium (Cr) revealed hormetic growth in the cases of Eichhornia crassipes [ 67 ], Salsola kali L. [ 68 ], Lemna minuta [ 69 ], Allium cepa L. [ 70 ] and Capsicium annum L. [ 71 ]. An hormetic response was observed as well, in the case of elements such as lanthanum (La) for Lonicera japonica [ 72 ], Oryza sativa L. [ 73 ] and Arabis paniculata [ 66 ], Pb for Pisum sativum [ 35 ], Brassica pekinensis [ 74 ] and Dianthus carthusianorum [ 60 ], Hg for Anthyllis vulneraria [ 75 ] and Helianthus tuberosus [ 76 ], palladium (Pd) for P. sativum L. [ 77 ], platinum (Pt) for Arabidopsis thaliana [ 78 ], uranium (U) for Schizachyrium scoparium [ 79 ], Zn for Thlaspi caerulescens [ 80 ], Sedum alfredii [ 57 ] and Arabis paniculata [ 66 ].…”
Section: Hormesis As a Biological Phenomenon In The Context Of Orgmentioning
confidence: 99%
“…Cadmium tolerance is related with declines of the internal Cd accumulation [8] but some plant species are able to sustain growth or even improve their growth and functioning under Cd exposure, despite a high Cd accumulation in roots and shoots [9][10][11]. Foliar Cd content above 0.01 % dry biomass (100 μg g −1 ) is considered extraordinary and a limit value for Cd hyperaccumulation [7,12,13].…”
Section: Introductionmentioning
confidence: 99%